Robotic Process Automation in purchasing and supply management: A multiple case study on potentials, barriers, and implementation. Issue 1 (January 2022) - Flechsig, Christian; Anslinger, Franziska; Lasch, Rainer
Abstract: Robotic Process Automation (RPA) has received growing attention within the digital transformation as this cutting-edge technology automates human behavior and promises high potentials. However, the adoption in purchasing and supply management (PSM) is still in its infancy and has hardly been explored, particularly in the public sector. Based on a multiple case study including 19 organizations of the public and private sector, this paper narrows that gap and presents comprehensive insights into potentials, barriers, suitable processes, and best practices and components for RPA implementation. The findings indicate that adoption depends on the organizations' digital procurement readiness and maturity. Application areas of RPA enlarge with increasing experience and range from transactional and operative tasks within the procure-to-pay process to more strategic use cases in sourcing and supply relationship management. Potentials mainly comprise employee reliefs, cost savings, and increased operational efficiency and quality. We uncover multiple technical, organizational, and environmental barriers related to IT infrastructure and human resources, internal communication, financial resources, top management support, organizational structures, supplier-related issues, and government regulations. Furthermore, our study indicates several differences between the private and public sectors for RPA implementation. We outline implications for the emerging research on RPA and pivotal directions for organizational practice. Highlights: Uncovers and categorizes 16 potentials and 25 barriers of RPA in PSM. Proposes a three-stage model for initial RPA implementation. Derives various PSM application areas and best practices to cope with the barriers. Compares private and public procurement organizations regarding RPA. Indicates that RPA adoption depends on digital procurement readiness and maturity.